Patient-relativity in morality - HAMMERTON, Matthew (Institutional Knowledge at Singapore Management University, 2016)
It is common to distinguish moral rules, reasons, or values that are agent-relative from those that are agent-neutral. One can also distinguish moral rules, reasons, or values that are moment-relative from those that are moment-neutral. In this article, I introduce a third distinction that stands alongside these two distinctions—the distinction between moral rules, reasons, or values that are patient-relative and those that are patient-neutral. I then show how patient-relativity plays an important role in several moral theories, gives us a better understanding of agent-relativity and moment-relativity, and provides a novel objection to Derek Parfit’s “appeal to full relativity” argument.